A genome-wide transcriptome and translatome analysis of Arabidopsis transposons identifies a unique and conserved genome expression strategy for Ty1/Copia retroelements - Oberlin, Stefan; Sarazin, Alexis; Chevalier, Clément; Voinnet, Olivier; Marí-Ordóñez, Arturo (Genome Research, 2017)
Retroelements, the prevalent class of plant transposons, have major impacts on host genome integrity and evolution. They produce multiple proteins from highly compact genomes and, similar to viruses, must have evolved original strategies to optimize gene expression, although this aspect has been seldom investigated thus far. Here, we have established a high-resolution transcriptome/translatome map for the near-entirety of Arabidopsis thaliana transposons, using two distinct DNA methylation mutants in which transposon expression is broadly de-repressed. The value of this map to study potentially intact and transcriptionally active transposons in A. thaliana is illustrated by our comprehensive analysis of the cotranscriptional and translational features of Ty1/Copia elements, a family of young and active retroelements in plant genomes, and how such features impact their biology. Genome-wide transcript profiling revealed a unique and widely conserved alternative splicing event coupled to premature termination that allows for the synthesis of a short subgenomic RNA solely dedicated to production of the GAG structural protein and that preferentially associates with polysomes for efficient translation. Mutations engineered in a transgenic version of the Arabidopsis EVD Ty1/Copia element further show how alternative splicing is crucial for the appropriate coordination of full-length and subgenomic RNA transcription. We propose that this hitherto undescribed genome expression strategy, conserved among plant Ty1/Copia elements, enables an excess of structural versus catalytic components, mandatory for mobilization.
10.1101/gr.220723.117